2019
DOI: 10.3390/antibiotics8030095
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Selected Bacteria and Yeasts to Control Vibrio spp. in Live Food

Abstract: Vibrio species are a significant causative of mass mortality in mariculture worldwide, which can quickly accumulate in live food and transmit into the larval gut. With restrictions on the use of antibiotics in aquaculture, finding a proper solution to reduce the risk of Vibriosis is vital. This study aimed to evaluate the susceptibility of Vibrio harveyi, V. campbellii, V. anguillarum, and V. parahaemolyticus to twenty-six bacterial and yeast strains and use the beneficial ones to enrich live food (Branchiopod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
13
1
Order By: Relevance
“…Despite the previous observations, antibiotic treatment can reduce bacterial load in live feeds but cannot prevent the live feeds from being recolonized within a short period [27], thus suggesting the need to find other therapeutic alternatives. In addition, well-documented toxic effects of florfenicol on fish and crustacean larvae [69][70][71][72] indicate the urgent need for considering the use of alternative strategies to control pathogenic bacteria in live feeds administered to marine fish aquaculture, including bacteriophages, probiotics, and natural products [42,73,74]. In a recent study, probiotics, organic acids, and essential oils were demonstrated to be effective at controlling the pathogenic activity of vibrios on A. franciscana nauplii [75].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the previous observations, antibiotic treatment can reduce bacterial load in live feeds but cannot prevent the live feeds from being recolonized within a short period [27], thus suggesting the need to find other therapeutic alternatives. In addition, well-documented toxic effects of florfenicol on fish and crustacean larvae [69][70][71][72] indicate the urgent need for considering the use of alternative strategies to control pathogenic bacteria in live feeds administered to marine fish aquaculture, including bacteriophages, probiotics, and natural products [42,73,74]. In a recent study, probiotics, organic acids, and essential oils were demonstrated to be effective at controlling the pathogenic activity of vibrios on A. franciscana nauplii [75].…”
Section: Discussionmentioning
confidence: 99%
“…In our in silico analysis, L. buchneri exhibited parasitic interaction limiting the pathogen surivival. Another shortlisted species, L. sakei , isolated from fish and meat products ( Lim et al., 2014 ), reduce the count of Vibrio species in different live prey such as Artemia franciscana , Brachionus plicatilis , and Tigriopus japonicas ( Sahandi et al., 2019 ). It has been reported that L. sakei showed a stronger killing effect on pathogenic V. parahaemolyticus , making it a promising candidate in controlling vibriosis ( Le and Yang, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We developed a strain-specific genome-scale metabolic model concentrating on Lactobacilli , Bacilli , and Lactococci genera having closed-genome sequences. Moreover, the species from these genera have demonstrated health advantages ( Sahandi et al., 2019 ). The pathogenic strain V. harveyi employed in this study is associated with infections in shellfish, finfish, corals, and molluscs, leading to substantial economic loss to the farmed species in both brackish water and marine aquaculture ( Darshanee Ruwandeepika et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of probiotics to inhibit the growth of Vibrio spp. might be a good method for preventing the pathogen and may also reduce its chances of antibiotic resistance 26 .…”
Section: Antimicrobial Disc Sensitivity Testmentioning
confidence: 99%